2019
DOI: 10.1287/mnsc.2018.3199
|View full text |Cite
|
Sign up to set email alerts
|

Communicating with Warmth in Distributive Negotiations Is Surprisingly Counterproductive

Abstract: When entering into a negotiation, individuals have the choice to enact a variety of communication styles. We test the differential impact of being "warm and friendly" versus "tough and firm" in a distributive negotiation when first offers are held constant and concession patterns are tracked. We train a natural language processing algorithm to precisely quantify the difference between how people enact warm and friendly versus tough and firm communication styles. We find that the two styles differ primarily in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 82 publications
1
24
1
Order By: Relevance
“…We posed as a potentially interested buyer sending offer messages to participants and randomly varied the first-offer amount. We closely followed the design used in Jeong, Minson, Yeomans, and Gino (2019). We created a fictitious Gmail account with a gender-neutral name (“Riley Stone”), which allowed us to send all messages from the same source and to track responses.…”
Section: Methodsmentioning
confidence: 99%
“…We posed as a potentially interested buyer sending offer messages to participants and randomly varied the first-offer amount. We closely followed the design used in Jeong, Minson, Yeomans, and Gino (2019). We created a fictitious Gmail account with a gender-neutral name (“Riley Stone”), which allowed us to send all messages from the same source and to track responses.…”
Section: Methodsmentioning
confidence: 99%
“…In human-human e-negotiations, Belkin et al [7] showed that the linguistic expression of happiness was associated with submissiveness whereas the linguistic expression of anger with dominance. A behavior being perceived as more dominant achieved higher individual negotiation gains [7] and behavior taking on a tough and firm communication style resulted in higher economic outcomes and more beneficial counteroffers [25]. In line with this are findings in a multi-modal setting, where in human-agent negotiations virtual agents expressing dominant hand gestures and body postures convinced elderly more often to follow their suggestions than submissive agents [35].…”
Section: Effect Of Dominance On Negotiation Outcomesmentioning
confidence: 76%
“…This is useful as a robustness check when there is wide variance in document length. For example take the following two texts (this data, borrowed from (Jeong et al, 2018) is included in the package):…”
Section: Library(politeness)mentioning
confidence: 99%
“…In addition to the phone_offers dataset, we have included a smaller bowl_offers dataset (also from (Jeong et al, 2018)). Participants in this study were given similar instructions (i.e., communicate in a warm or tough style) but for a different negotiation exercise.…”
Section: Projecting Politeness Featuresmentioning
confidence: 99%